Social Worldviews and Personal Beliefs as Risk Factors for Radicalization: A Comparison Between Muslims and non-Muslims Living in Poland - Jakubowska, Urszula (International journal of conflict and violence, 2021)
This paper contributes to the understanding of the radicalization process. Muslim and non-Muslim residents of Poland were compared on their pro-terrorist attitudes toward sacrifice and non-sacrifice terrorism. We observed that acceptance of sacrifice terrorism and non-sacrifice terrorism are distinct but overlapping attitudes. These attitudes are explained by a separate configuration of social worldviews and personal beliefs. We found acceptance of non-sacrifice terrorism to be predicted by individual belief in a hostile world and the perception of low social support, whereas acceptance of sacrifice terrorism is determined by religious fundamentalism and authoritarianism. The separate beliefs underlying these two forms of pro-terrorist attitudes may indicate their different psychological functions. Acceptance of sacrifice terrorism serves as a defense of religion and culture, whereas acceptance of non-sacrifice terrorism serves to release personal frustration. This distinction may be used in terrorism prevention programs and/or de-radicalization programs. We also found that the risk of radicalization increases with the socio-cultural isolation of Muslims, decreases with age, and is particularly high for males.